Developing a Digital Civics Encyclopedia to Cultivate 3rd Grade of Elementary School Sttudents’ Resposibility - Verananda, Estela Werwin (International Journal Labs, 2021)
Background: One of the government's efforts to instill an attitude of responsibility to citizens in exercising their rights and obligations is to equip learners through classroom learning. One of the subjects that can pedagogically support social values related to the introduction of attitudes of responsibility in exercising rights and obligations is VAT. Aim: The researcher aims to develop the existing digital Civics encyclopedia for Grade 3rd students of Elementary School. Method: The method used in this research is Research and Development (R&D). Findings: Based on the results of an analysis of the student small group trial indicators, no revisions or improvements were made because the indicators with the lowest scores were in the category enough. Therefore, the last stage of the trial was a large group trial that produced a score of 84.09%. After going through several stages of trials, the application of digital encyclopedia of PPKn learning is ready to be implemented for learning by grade III students to instill an attitude of responsibility through the material obligations and rights in the home, school, and community